Treatment of extrusive luxation by intentional replantation - WILSON DENIS MARTINS, VANIA PORTELA DITZEL WESTPHALEN, CAMILA PAIVA PERIN, ULISSES XAVIER DA SILVA N (IAPD and Blackwell, 2007)
Luxations of the permanent teeth are divided into the following categories: subluxation, lateral luxation, intrusion and extrusion.